Identification and Characterization of Relict Olive Varieties (Olea europaea L.) in the Northwest of the Iberian Peninsula - Pilar Gago; Susana Boso; José-Luis Santiago; María-Carmen Martínez (Horticulturae, 2024)
Olives (Olea europaea L.) are an important crop in the Mediterranean Basin, but it is not well-known that they have also been grown in other areas, such as Galicia in northwestern Spain. Although commercial production ended long ago in this peripheral growing region, it remains home to olive resources that are well-adapted to the prevailing environmental conditions, providing a valuable but largely undocumented source of genetic variation. Following a survey of Galicia to locate examples of centuries-old olive trees, those detected were subjected to molecular characterization using a set of microsatellite markers, as well as full botanical characterization using the features established by the International Union for the Protection of New Varieties of Plants, along with others proposed by the present authors. These procedures allowed 11 undescribed varieties to be identified, which are new genetic resources that might be of use in olive improvement programs or studies of how the species adapts to different climates. The trees also underwent preliminary health checks, allowing disease-free specimens of each variety to be propagated. The addition of this material to the Community Plant Variety Office’s register of commercial varieties is underway.